Nonsingular terminal sliding mode control for micro-electro-mechanical gyroscope based on disturbance observer: Linear matrix inequality approach. (May 2022) - Jafari, Maryam; Mobayen, Saleh; Roth, Hubert; Bayat, Farhad
The aim of this article is to design a nonsingular terminal sliding mode control method based on disturbance observer for the stabilization of the micro-electro-mechanical systems under lumped perturbation. By using the nonsingular terminal sliding mode control scheme, the state trajectories of the system achieve the switching surface and approach to the origin in the finite time. Also, by utilizing the disturbance observer, the finite-time convergence of disturbance error is assured. In the process of design, the optimized coefficients of the sliding surface are calculated in the form of linear matrix inequality. Simulation results for a micro-electro-mechanical gyroscope are illustrated to exhibit the validity of the planned approach in comparison with the other methods.